Peran Kecerdasan Buatan (Artificial Intelligence) dalam Mendorong Inovasi Manajemen Pendidikan Islam di Era Revolusi Industri 4.0 - SODIK, AHMAD (Sekolah Tinggi Ilmu Tarbiyah Darul Fattah, 2024)
The industrial revolution 4.0 has driven the rapid development of digital technology, including artificial intelligence (AI). AI has great potential to transform Islamic education management to be more efficient and quality. The purpose of this study is to explore and map the role of AI in driving innovation in Islamic education management. This research uses a qualitative method with a literature study approach. Data were collected from various sources such as journals, books and research reports related to the topic of AI and Islamic education. The study results show that AI plays a role in automating administrative processes, improving the quality of learning through personalization, and opening up opportunities for the development of more adaptive Islamic education models. However, the implementation of AI requires careful preparation regarding IT infrastructure, human resources, and a multidisciplinary collaborative approach. It is concluded that with adequate preparation, AI can make a significant contribution to the innovation of the Islamic education system in the digital era. Further research is needed to formulate contextualized AI implementation guidelines in Islamic education settings.